2014
DOI: 10.1002/app.41431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drug and polymer molecular weight on drug release from PLGA‐mPEG microspheres

Abstract: This study investigated the effects of drug and polymer molecular weight on release kinetics from poly (G-co-glycolic acid)-methoxypoly(ethyleneglycol) (PLGA-mPEG) microspheres. Bovine serum albumin (BSA, 66 kDa), lysozyme (LZ, 13.4 kDa), and vancomycin (VM, 1.45 kDa) were employed as the model drugs, and encapsulated in PLGA-mPEG microspheres of different molecular weight. Release of macromolecular BSA was mainly dependent on diffusion of drug at/ near the surface of the matrix initially and dependent on degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…[86,145] Recently, Feng et al studied the release profile of PLGA/PEG microspheres with three different molecular weight drugs: vancomycin (VM, 1.45 kDa), lysozyme (LZ, 13.4 kDa) and bovine serum albumin (BSA, 66 kDa). [146] It was observed a fast burst release for VM-loaded PLGA/PEG microspheres, whereas for the other two drugs a controlled release was achieved. Further, LZ had a higher released amount than BSA during the same period of time.…”
Section: Drug Release From Poly(lactic-co-glycolic) Acid Delivery Sysmentioning
confidence: 94%
“…[86,145] Recently, Feng et al studied the release profile of PLGA/PEG microspheres with three different molecular weight drugs: vancomycin (VM, 1.45 kDa), lysozyme (LZ, 13.4 kDa) and bovine serum albumin (BSA, 66 kDa). [146] It was observed a fast burst release for VM-loaded PLGA/PEG microspheres, whereas for the other two drugs a controlled release was achieved. Further, LZ had a higher released amount than BSA during the same period of time.…”
Section: Drug Release From Poly(lactic-co-glycolic) Acid Delivery Sysmentioning
confidence: 94%
“…PLGA–mPEG [PLGA 9573 –mPEG 5000 (where 9573 is the Mw of PLGA, and 5000 is the Mw of mPEG), MW 14,573, lactide/glycolide (LA/GA) = 3:1' was synthesized in our laboratory and characterized by gel permeation chromatography, IR, 1 H‐NMR, and 13 C‐NMR spectroscopy . Poly(vinyl alcohol) (PVA; polymerization degree ≈ 1700 and hydrolysis degree ≈ 99%) from China National Medicines Corp., Ltd., was used as a stabilizer in the emulsion.…”
Section: Methodsmentioning
confidence: 99%
“…Unloaded microspheres prepared under the same conditions were applied in a degradation study as it was reported that unloaded microspheres degraded in a manner that was very similar to those loaded with the drugs. The degradation behavior of the microspheres was evaluated by the effects of MW reduction, total mass loss, morphology, and size changes with time on their incubation in PBS at 37°C, as described in our previous work . Unloaded microspheres which were applied for degradation analysis were incubated under the same conditions as those used for the drug‐release experiment.…”
Section: Methodsmentioning
confidence: 99%
“…[9] The microspheres Mw reduction, mass loss, and morphology change were examined and compared during the degradation period. After a week incubation, significant Mw reduction of the microspheres occurred, 85.32% of original Mw remained for PCL (25,000) microspheres, 79.42% for PCL (24,000) -mPEG (1,000) microspheres, 74.35% for PCL (22,000) -mPEG (3,000) microspheres, and 72.61% for PCL (20,000) -mPEG (5,000) microspheres. The Mw of the four types of microspheres decreased drastically with degradation time, as shown in Figure 3.…”
Section: In Vitro Degradation Studymentioning
confidence: 98%
“…All the microspheres exhibited an initial burst release around 14% of the total drug, which should largely due to the drug placed on the most superficial part of the microspheres as reported. The lysozyme loaded microspheres prepared by double emulsion evaporation method got a drug-in-matrix blending structure, and it was reported that the lysozyme release was mainly controlled by microspheres degradation/erosion rate, [22] faster degradation/erosion rate caused faster release rate, which explained the release diversity among the four types of microspheres. PCL-mPEG microspheres showed faster drug release rates than PCL microspheres after the initial burst release, and the rate difference came more obvious when the mPEG chain grew longer.…”
Section: In Vitro Release Studymentioning
confidence: 99%